A Comprehensive Insight into Potential Roles of Taurine on Metabolic Variables in Type 2 Diabetes: A Systematic Review - Vahid Maleki; Reza Mahdavi; Fatemeh Hajizadeh-Sharafabad; Mohammad Alizadeh (Tabriz University of Medical Sciences, 2020)
Background: Prevention and management of type 2 diabetes mellitus (T2DM), as a major, non-communicable disease with increasing prevalence, is one of the major human challenges. The aim of this systematic review is to summarize current studies about the potential roles of taurine in T2DM, to identify knowledge gaps and to provide recommendations for the way forward. Methods: The literature search was performed in PubMed, SCOPUS, Embase, ProQuest and Google Scholar electronic databases to December 2019. All studies investigating the impacts of taurine in T2DM which met the inclusion criteria were eligible. Results: Out of 1381 articles found in the search, 12 were included. Findings of taurine supplementation on glycemic control in T2DM showed improving effect of taurine on fasting and postprandial blood glucose, serum insulin level, insulin resistance, function of beta cells, and insulin sensitivity. But, the results for Hemoglobin A1c and homeostatic model assessment-insulin resistance (HOMA-IR) were contradictory. Also, taurine reduced total cholesterol, TG, and low density lipoprotein-cholesterol (LDL-C) levels, however, the evidence on high density lipoprotein-cholesterol (HDL-C) was insufficient. Findings didn not support antioxidative role of taurine in T2DM. Conclusion: As a whole, taurine has potential to improve glycemic status and dyslipidemia. However, more clinical trials are needed to explore precise mechanisms underlying taurine on metabolic variables, oxidative stress, and inflammatory biomarkers, according to the recommendations for future directions.